Determination of chlorhexidine retention in different oral sites using matrix-assisted laser desorption/ionization-time of flight mass spectrometry. (February 2020) - Reda, Bashar; Hollemeyer, Klaus; Trautmann, Simone; Hannig, Matthias; Volmer, Dietrich A.
Highlights: MALDI-TOF MS is a selective and sensitive method for chlorhexidine detection. Chlorhexidine retains in the mouth at micrograms per milliliter levels for 11 h. Dental pellicle and oral mucosa are the main reservoirs for chlorhexidine. Chlorhexidine retention in the saliva is clearly lower compared to other oral sites. MALDI-TOF can be considered as a promising method to detect antibacterial agents. Abstract: Objective: The aim of this study was to determine chlorhexidine retention in different oral sites after a one-time 30 s mouth rinsing. Design: Five volunteers were asked to rinse their mouth with 10 ml of 0.2 % chlorhexidine digluconate for 30 s. After rinsing, samples were collected from the interdental area, buccal dental pellicle, anterior labial and posterior buccal mucosa, and saliva with a microbrush at five-time points within 24 h. Retention of chlorhexidine was measured using matrix-assisted laser desorption/ionization-time of flight mass spectrometry with a quantification limit of 15 ng/ml. Results: Chlorhexidine remained in the oral cavity at micrograms per milliliter levels for 11 h after mouth rinsing and was even detected 24 h after application. The results showed a distinct decline of intraoral chlorhexidine levels during the first 6 h after rinsing and it was then retained at low concentrations for at least 24 h. Conclusions: The dental pellicle and oral mucosa were favorable sites for chlorhexidine retention. The novel method used for chlorhexidine determination offered excellent quantification limits and readily permitted quantification of chlorhexidine.